The Prevention of Mental Disorders has a Bright Future - Ajdacic-Gross, Vladeta (Frontiers in Public Health, 2014)
This article takes four looks at the status of prevention in psychiatry. The first glance is critical, shaped by disappointment at the slow progress in the understanding of psychiatric diseases and the lack of promise in prevention. The second look is less humble. It characterizes and acknowledges the efforts made so far. The third and the fourth perspectives optimistically announce a new age in research and prevention. Breakthroughs, whose contours are already appearing on the horizon today, will transform the prevention of psychiatric diseases into a success story within the next 10–15 years.